Yishen Tongbi decoction attenuates inflammation and bone destruction in rheumatoid arthritis by regulating JAK/STAT3/SOCS3 pathway - Xu, Jia; Jiao, Wei; Wu, Dan-Bin; Yu, Jia-Hui; Liu, Li-Juan; Zhang, Ming-Ying; Chen, Guang-Xing (Frontiers in Immunology, 2024)
Yishen-Tongbi Decoction (YSTB), a traditional Chinese prescription, has been used to improve syndromes of rheumatoid arthritis (RA) for many years. Previous research has shown that YSTB has anti-inflammatory and analgesic properties. However, the underlying molecular mechanism of the anti-RA effects of YSTB remains unclear.The purpose of this research was to investigate how YSTB affected mice with collagen-induced arthritis (CIA) and RAW264.7 cells induced with lipopolysaccharide (LPS).The findings show that YSTB could significantly improve the clinical arthritic symptoms of CIA mice (mitigate paw swelling, arthritis score, thymus and spleen indices, augment body weight), downregulated expression of pro-inflammatory cytokines like tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β), IL-6 and IL-17, while upregulated the level of anti-inflammatory like IL-10 and transforming growth factor-β (TGF-β). Meanwhile, YSTB inhibits bone erosion and reduces inflammatory cell infiltration, synovial proliferation, and joint destruction in CIA mice. In addition, we found that YSTB was able to suppress the LPS-induced inflammation of RAW264.7 cells, which was ascribed to the suppression of nitric oxide (NO) production and reactive oxygen species formation (ROS). YSTB also inhibited the production of inducible nitric oxide synthase and reduced the releases of pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in LPS-induced RAW264.7 cells.Furthermore, the phosphorylation expression of JAK2, JAK3, STAT3, p38, ERK and p65 protein could be suppressed by YSTB, while the expression of SOCS3 could be activated.Taken together, YSTB possesses anti-inflammatory and prevention bone destruction effects in RA disease by regulating the JAK/STAT3/SOCS3 signaling pathway.